1999
DOI: 10.1021/jm9708442
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Structure−Activity Relationship of Interleukin 1-β Converting Enzyme Inhibitors:  A Comparative Molecular Field Analysis Study

Abstract: A three-dimensional quantitative structure-activity relationship (QSAR) study using the comparative molecular field analysis (CoMFA) method was performed on a series of interleukin 1-beta converting enzyme (ICE) inhibitors. The compounds studied have been reported to be time-dependent inhibitors of ICE. This study was performed using 49 compounds, in which the CoMFA models were developed using a training set of 39 compounds. All the compounds were modeled using the X-ray crystal structure of tetrapeptide aldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
(76 reference statements)
0
35
0
Order By: Relevance
“…PLS is normally used in combination with cross-validation to obtain the optimum number of components. This ensures that the QSAR equations are selected based on their ability to predict the data rather than to fit the data [33]. From the factor loading table (rotated component matrix), variables with high loading (> 0.7) in such factors where the binding affinity shows high or moderate loading were selected for the PLS regression.…”
Section: Model Developmentmentioning
confidence: 99%
“…PLS is normally used in combination with cross-validation to obtain the optimum number of components. This ensures that the QSAR equations are selected based on their ability to predict the data rather than to fit the data [33]. From the factor loading table (rotated component matrix), variables with high loading (> 0.7) in such factors where the binding affinity shows high or moderate loading were selected for the PLS regression.…”
Section: Model Developmentmentioning
confidence: 99%
“…Table 7 shows that the best statistical quality along with prediction statistics with ETA descriptors is found in case of GFA-MLR equation. (1, 5, 9, 13, 17, 21, 25, 29, 33, 7, 41), (2, 6, 10, 14, ..., 34, 38), ..., (4,8,12,16,20,24,28,32,36,40). …”
Section: Resultsmentioning
confidence: 99%
“…PLS is normally used in combination with cross-validation to obtain the optimum number of components. This ensures that the QSAR equations are selected based on their ability to predict the data rather than to fit the data [40]. In case of FA-PLS analysis on the present data set, factor loading table obtained from factor analysis was used for primary variable screening.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the routine has been reported by several workers (see, e.g., [33][34][35]) but is quite complex in operation [36], involving the inclusion of weighted field-fit energy penalties as additional parameters in the Tripos force field. More recently, Paretti et al have described a procedure that is analogous to that reported here [20] but that uses Monte Carlo and simplex procedures for the generation of the alignments, rather than a GA, and PLS analysis of N×N similarity matrices, rather than CoMFA and CoMSIA.…”
Section: Discussionmentioning
confidence: 99%